2021
DOI: 10.1080/19490976.2021.1939598
|View full text |Cite
|
Sign up to set email alerts
|

The commensal bacterium Lactiplantibacillus plantarum imprints innate memory-like responses in mononuclear phagocytes

Abstract: Gut microbiota is a constant source of antigens and stimuli to which the resident immune system has developed tolerance. However, the mechanisms by which mononuclear phagocytes, specifically monocytes/macrophages, cope with these usually pro-inflammatory signals are poorly understood. Here, we show that innate immune memory promotes anti-inflammatory homeostasis, using as model strains of the commensal bacterium Lactiplantibacillus plantarum. Priming of monocytes/ macrophages with bacteria, especially in its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…A recent study found that priming of human monocytes or murine bone marrow-derived macrophages (mBMMs) with live L. plantarum or L. casei bacteria prompts a tolerant memory-like state following secondary stimulus exposure. 27 Tolerance induction was bacteria dose-dependent and it was not reciprocated when mBMMs were primed with L. plantarum conditioned medium. 27 We cannot rule out the possibility that using live L. reuteri bacteria would lead to a different DC phenotype, however, studying bacteria-derived metabolites is equally relevant as they widely penetrate host tissues and small intestine is particularly prone to host-microbial metabolic exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that priming of human monocytes or murine bone marrow-derived macrophages (mBMMs) with live L. plantarum or L. casei bacteria prompts a tolerant memory-like state following secondary stimulus exposure. 27 Tolerance induction was bacteria dose-dependent and it was not reciprocated when mBMMs were primed with L. plantarum conditioned medium. 27 We cannot rule out the possibility that using live L. reuteri bacteria would lead to a different DC phenotype, however, studying bacteria-derived metabolites is equally relevant as they widely penetrate host tissues and small intestine is particularly prone to host-microbial metabolic exchange.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Tolerance induction was bacteria dose-dependent and it was not reciprocated when mBMMs were primed with L. plantarum conditioned medium. 27 We cannot rule out the possibility that using live L. reuteri bacteria would lead to a different DC phenotype, however, studying bacteria-derived metabolites is equally relevant as they widely penetrate host tissues and small intestine is particularly prone to host-microbial metabolic exchange. 1 Also, probiotic bacteria like lactobacilli have been shown to prompt the production of innate cell-associated cytokines through both cell-surface components and secreted metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors can contribute to the onset of these diseases. Dysbiosis-induced oxidative stress disrupts the intricate equilibrium of gut homeostasis, leading to an increased degree of immunological dysregulation ( Pellon et al, 2021 ). The identification of fresh therapeutic targets for the treatment and prevention of intestinal illnesses may be possible if a comprehensive understanding of the underlying processes governing this interaction is achieved.…”
Section: Gut Microbiota-mediated Oxidative Stress and Bowel Diseasementioning
confidence: 99%
“…exhibit remarkable antimicrobial activity against pathogenic bacteria thanks to the production of bacteriocins, reactive oxygen species, biosurfactants and exopolysaccharides with anti-biofilm activity (20-22). Lactiplantibacillus plantarum (LP) and Lacticaseibacillus rhamnosus (LR) belong to the human microbiota (23, 24) and are present in food as probiotics. Previous studies have demonstrated their anti-pathogen properties against Streptococcus mutans, Candida spp., Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella sp., and uropathogenic Escherichia coli (20, 25-27).…”
Section: Introductionmentioning
confidence: 99%